2023
DOI: 10.1021/acs.cgd.3c00634
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Dynamics of Quinacridone Polymorphs: A Combined Raman and Computational Approach

Andrea Giunchi,
Lorenzo Pandolfi,
Raffaele G. Della Valle
et al.

Abstract: Polarized low-frequency Raman microscopy and a posteriori dispersion-corrected density functional simulations are combined to investigate the lattice vibrations of the α I , β, and γ polymorphs of the model organic semiconductor quinacridone, which are known to display different optical and electronic properties. The comparison between experiments and calculations allows for unambiguous mode assignment and identification of the scattering crystal faces. Conversely, the agreement between simulations and experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…These noncovalent interactions affect the arrangement structure of donor and acceptor molecules in the cocrystal, which further influences the optoelectronic properties . For example, Huang et al reported that water molecules within ternary organic cocrystals were essential for the formation of many types of hydrogen bonds (e.g., N–H···O, N···H–O, N–H···N, and C–H···O).…”
Section: Introductionmentioning
confidence: 99%
“…These noncovalent interactions affect the arrangement structure of donor and acceptor molecules in the cocrystal, which further influences the optoelectronic properties . For example, Huang et al reported that water molecules within ternary organic cocrystals were essential for the formation of many types of hydrogen bonds (e.g., N–H···O, N···H–O, N–H···N, and C–H···O).…”
Section: Introductionmentioning
confidence: 99%